On isomorphisms of small order bi-Cayley graphs
For a finite group G and a subset S⊇G (possibly, S contains the identity), the bi-Cayley graph BCay(G,S) of G with respect to S is the graph with vertex set G× 0,1 and with edge set (x,0),(sx:,1)|x ∈ G, s ∈ S